Accounting Principles A Business Perspective - Hermanson, Roger H.; Edwards, James D.; Maher, Michael W. (Open textbook library., 2011)
Accounting Principles: A Business Perspective uses annual reports of real companies to illustrate many of the accounting concepts in use in business today. Gaining an understanding of accounting terminology and concepts, however, is not enough to ensure your success. You also need to be able to find information on the Internet, analyze various business situations, work effectively as a member of a team, and communicate your ideas clearly. This text was developed to help you develop these skills.